2020
DOI: 10.1002/fft2.34
|View full text |Cite
|
Sign up to set email alerts
|

Transplanting fecal material from wild‐type mice fed black raspberries alters the immune system of recipient mice

Abstract: By constantly stimulating intestinal immunity, gut microbes play important regulatory roles, and their possible involvement in human physical and mental disorders beyond intestinal diseases suggests the importance of maintaining homeostasis in the gut microbiota. Both transplantation of fecal microbiota and dietary interventions have been shown to restore microbial homeostasis in recipients. In the current study with wild-type mice, we combined these two approaches to determine if transplanting fecal material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…Metabolites of gut microbiota (e.g., butyric acid, pentanoate, and butyrate) also induced Treg cell differentiation [ 158 ], increased the secretion of anti-tumor cytokines (e.g., IFN-γ and TNF-α) by CD8 + T cells, and enhanced the anti-tumor responses of antigen-specific CTLs and CAR-T cells [ 159 ]. In collaboration with the Wang lab, we found that feeding black raspberries, a natural product, significantly induced distinct changes in murine gut microbiota, increased the abundance of anti-inflammatory microbial species (e.g., Akkermansia and Desulfovibrio ), activated anti-tumor immune cells (e.g., NK cells), and enhanced those cells’ anti-tumor immune responses [ 160 163 ]. Conversely, dysbiosis of gut microbiota in mice increased susceptibility to colon tumors because it overstimulated CD8 + T cells, which in turn promoted chronic inflammation and early T cell exhaustion, thereby reducing the cells’ anti-tumor immune response [ 154 ].…”
Section: Potential Role Of Notch Signaling In Tumor Immunity Mediated...mentioning
confidence: 99%
“…Metabolites of gut microbiota (e.g., butyric acid, pentanoate, and butyrate) also induced Treg cell differentiation [ 158 ], increased the secretion of anti-tumor cytokines (e.g., IFN-γ and TNF-α) by CD8 + T cells, and enhanced the anti-tumor responses of antigen-specific CTLs and CAR-T cells [ 159 ]. In collaboration with the Wang lab, we found that feeding black raspberries, a natural product, significantly induced distinct changes in murine gut microbiota, increased the abundance of anti-inflammatory microbial species (e.g., Akkermansia and Desulfovibrio ), activated anti-tumor immune cells (e.g., NK cells), and enhanced those cells’ anti-tumor immune responses [ 160 163 ]. Conversely, dysbiosis of gut microbiota in mice increased susceptibility to colon tumors because it overstimulated CD8 + T cells, which in turn promoted chronic inflammation and early T cell exhaustion, thereby reducing the cells’ anti-tumor immune response [ 154 ].…”
Section: Potential Role Of Notch Signaling In Tumor Immunity Mediated...mentioning
confidence: 99%
“…Anthocyanins are flavonoid compounds formed by a combination of anthocyanins and sugars. Plant anthocyanins have apparent antioxidant [ 9 , 10 ] and anti-inflammatory [ 11 , 12 ] properties. According to the existing literature, anthocyanins can be used as functional active ingredients and therapeutic agents for the prevention and treatment of diseases [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer is the second leading cause of cancer death in both sexes in the United States [ 1 ]. Many factors are associated with the development of colorectal cancer, such as “unhealthy” diets [ 2 - 6 ], gut inflammation [ 7 - 10 ], and microbial dysbiosis [ 11 - 14 ].…”
Section: Introductionmentioning
confidence: 99%